2015
DOI: 10.1016/j.jped.2015.01.008
|View full text |Cite|
|
Sign up to set email alerts
|

Association between physical activity, participation in Physical Education classes, and social isolation in adolescents

Abstract: It was concluded that participation in Physical Education classes is associated with reduced social isolation among female adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 24 publications
3
25
0
6
Order By: Relevance
“…In the researched literature, only one study was identified with Brazilian adolescents that sought to partially investigate this association (Santos et al, 2015). The authors, in analyzing the social isolation, through the feeling of loneliness and number of friends, in more than 4000 adolescents of Pernambuco, did not find associations between loneliness and habitual PA, nor with the participation in the classes of physical education.…”
Section: Discussionmentioning
confidence: 99%
“…In the researched literature, only one study was identified with Brazilian adolescents that sought to partially investigate this association (Santos et al, 2015). The authors, in analyzing the social isolation, through the feeling of loneliness and number of friends, in more than 4000 adolescents of Pernambuco, did not find associations between loneliness and habitual PA, nor with the participation in the classes of physical education.…”
Section: Discussionmentioning
confidence: 99%
“…Included studies were carried out between 2001 8-14 and 2015 15 ; most of them were performed in 2011 (12 studies) 16,17,[26][27][28][29][30][31][18][19][20][21][22][23][24][25] . Twenty studies were performed between 2011 and 2015 15,16,[25][26][27][28][29][30][31][32][33][34]17,[35][36][37][38][39][40][41][42][43][18][19][20][21][22][23][24] . Most of included studies were located in the South and Northeast regions of Brazil: 22 (35.5%) 8,9,[40][41]…”
Section: Resultsmentioning
confidence: 99%
“…Outro fator que está relacionado com a adoção de uma rotina sedentária é o isolamento social entre os adolescentes. Pesquisas relatam que jovens que têm uma relação social fora do horário escolar realizam mais exercícios físicos (44) . Isso pode ser explicado porque o apoio recebido pela família, amigos e professores é fundamental para a adoção de prática de atividades físicas (24,25,45) .…”
Section: De Acordo Com a Organizaçãounclassified
“…Além disso, estudos sugerem que a baixa competência motora, que pode ser definida como a capacidade de realizar atividades físicas em seus variados graus, tem sido relacionada com a menor prática de exercícios entre os jovens (46) . (44,47,48) , sendo as aulas de educação física um cenário ideal nesse processo (44) . ambientais, pessoais, físicos (7,25,26,47) , demográficos e psicológicos (25,26) .…”
Section: De Acordo Com a Organizaçãounclassified